Study on high sensitivity measurement method of hydrogen sulfide gas under long optical path - Chen, Shuwang; Song, Tongtong; Song, Shuli; Yin, Xiaowei; Wang, Zhenzhen (SPIE, 2019)
The small amount of hydrogen sulfide gas generated during the oil exploitation process is enough to cause great harm to the human body and mining equipment. It is necessary to detect hydrogen sulfide gas timely and accurately. Based on the principle of spectral absorption, a new method for detecting the concentration of hydrogen sulfide gas with high sensitivity is studied. According to Lambert Beer's law, increasing the optical path can enhance the intensity of the absorbed signal, thereby proposing a method using a long path gas absorption cell and increasing the sensitivity of the system detection. The improved Herriot absorption cell is used to make multiple round trips of light in the air chamber, which can obtain a longer absorption path and improve detection accuracy. The chamber is designed and simulated to test the practicality and accuracy. The light source part uses a Bragg fiber grating to modulate the LED broadband light source into a narrow-band light source, thereby reducing cost and enhancing practicability. The obtained light source is modulated and filtered, and the reference optical path is set, and then the dual optical path difference method is combined to eliminate the systematic error caused by noise interference and source fluctuation. The second harmonic in output signal is extracted by the lock-in amplifier, and then the gas concentration is inverted. At the same time, an adaptive algorithm is used to maintain the stability of the light source temperature, which can avoid the effects of temperature changes. The simulation experiments show that the long-range high-sensitivity measurement method of hydrogen sulfide greatly improves the measurement accuracy, and can be effectively applied to the on-line accurate detection of low-concentration hydrogen sulfide gas.